Biodiversity of Byram Mangrove Forest Pulau Pinang (The State Forestry Department of Penang, 2010)
Byram Forest Reserve and its surrounding area consist mainly of mangroves, fresh and brackish water ponds or rivers and mudflats. Though there is a landfill (rubbish dumpsite) in the area - Pulau Burung landfill, this has never been a reason for the birds not to flood into the area. Hence the bird have been coming more and more each year, especially during the migratory season. This is a good place to see the terns hunting for food especially during early morning and lat evening. They fly gracefully back and forth along the ponds while diving tp catch their food. This forest still holds some important mangrove specialist such as the grey tit and oriental white eye. It is important that this forest remains, as if it is not all this species will be out of Penang's list forever.